Cerebral tau is elevated after aneurysmal subarachnoid haemorrhage and associated with brain metabolic distress and poor functional and cognitive long-term outcome. Issue 1 (16th April 2014) - Helbok, Raimund; Schiefecker, Alois; Delazer, Margarete; Beer, Ronny; Bodner, Thomas; Pfausler, Bettina; Benke, Thomas; Lackner, Peter; Fischer, Marlene; Sohm, Florian; Hackl, Werner; Stover, John F; et al.
Abstract : Background: Recent evidence suggests axonal injury after aneurysmal subarachnoid haemorrhage (aSAH). The microtubule-associated protein, tau, has been shown to be elevated in the cerebrospinal fluid after aSAH, however, brain extracellular tau levels and their relation to long-term neurological and cognitive outcomes have not been investigated. Methods: Serial cerebral microdialysis (CMD) samples were collected from 22 consecutive aSAH patients with multimodal neuromonitoring to determine CMD-total-tau by ELISA. CMD-total-tau was analysed considering other brain metabolic parameters, brain tissue oxygen tension (Pb tO2 ), and functional and neuropsychological outcome at 12 months. All outcome models were analysed using generalised estimating equations with an autoregressive working correlation matrix to account for multiple measurements of brain extracellular proteins per subject. Results: CMD-total-tau levels positively correlated with brain extracellular fluid levels of lactate (r=0.40, p<0.001), glutamate (r=0.45, p<0.001), pyruvate (r=0.26, p<0.001), and the lactate-pyruvate ratio (r=0.26, p<0.001), and were higher in episodes of hypoxic (Pb tO2 <20 mm Hg) brain extracellular lactate elevation (>4 mmol/L) (p<0.01). More importantly, high CMD-total-tau levels were associated with poor functional outcome (modified Rankin Scale ≥4) 12 months after aSAH even after adjusting for disease severity and age (p=0.001). A similar association was found with 3/5 neuropsychological tests indicative of impairments in cognition, psychomotor speed, visual conceptualisation and frontal executive functions at 1 year after aSAH (p<0.01). Conclusions: These results suggest that CMD-total tau may be an important biomarker for predicting long-term outcome in patients with severe aSAH. The value of axonal injury needs further confirmation in a larger patient cohort, preferably combined with advanced imaging techniques.